The Production of Polyhydroxyalkanoate (PHA) Bioplastic from Palm Oil Mill Effluent (POME) using Pseudomonas aeruginosa - Hasnah Ulia; Selfa Dewati Samah; Enny Nurmalasari (Jurnal Kimia Sains dan Aplikasi, 2025)
Biodegradable plastics were continuously developed to replace non-degradable plastics. One type of bioplastic that was used was poly(hydroxyalkanoate) (PHA). In this study, PHA was synthesized using Palm Oil Mill Effluent (POME) and the bacterium Pseudomonas aeruginosa through a fed-batch (aerobic–anaerobic) fermentation process over six days. The study aimed to evaluate the use of POME as the sole carbon source for PHA synthesis by Pseudomonas aeruginosa through a fed-batch aerobic–anaerobic fermentation process. The total substrate volumes used in this study were 30, 60, and 90% (v/v), which were gradually added (fed-batch) at rates of 5, 10, and 15% (v/v)/day over the six-day fermentation period. The analytical results showed significant reductions in BOD (Biological Oxygen Demand), COD (Chemical Oxygen Demand), ammonia (NH3), and total suspended solids (TSS) after the fermentation process, indicating that organic and chemical compounds were degraded during fermentation. PHA production from POME showed that the maximum yield occurred on the third day, with 16.89 g/kg dry biomass and a PHA concentration of 9.089 wt% (1.53 g/kg) from a total substrate volume of 9 L. The fermentation process reached the exponential phase on the third day, declined on the fourth day, and stabilized by the sixth day, with an average yield of 5.248 wt%. Characterization using X-ray diffraction (XRD) confirmed that the produced PHA had a structure consistent with standard PHA. Further analysis of water absorption and biodegradability showed fluctuating results, with the best performance observed at a 5% concentration, indicating low water absorption and good biodegradability. In addition, the bioplastic produced had a tensile strength of 554.32 MPa and a modulus of elasticity of 5834.95 MPa.